Design of a donation crowdfunding website using PHP and MySQL - Windiarto, Elisha; Prananingrum , Lely (Privietlab, 2025)
The advancement of Internet technology has given rise to various digital innovations, including crowdfunding platforms that facilitate online fundraising. The Klik Amal website was developed as a medium for donations, fundraising, and sedekah subuh (pre-dawn alms) in an efficient manner to encourage public participation and social awareness. This website was built using the PHP programming language and a MySQL database, supported by XAMPP and Visual Studio Code on Windows 11 operating system. The system is equipped with three main features and is integrated with Midtrans payment services, which support QRIS, e-wallets, and Virtual Accounts. The SDLC waterfall model was used for development, covering analysis, design, implementation, testing, and maintenance. The development results show that the Klik Amal website is user-friendly, responsive, and easily accessible. This system is expected to serve as a practical and beneficial digital medium for sharing kindness among users. The Klik Amal website has been hosted at the link https://klikamal.my.id/